전단 자극에 의한 심방 근세포 칼슘 웨이브의 발생 : Phospholipase C-이노시톨 1,4,5-삼인산 수용체 신호전달의 역할 - 김준철(Joon-Chul Kim); 우선희(Sun-Hee Woo) (Yaghag-hoi-ji, 2015)
Cardiac myocytes are subjected to fluid shear stress during each contraction and relaxation. Under pathological conditions, such as valve disease, heart failure or hypertension, shear stress in cardiac chamber increases due to high blood volume and pressure. The shear stress induces proarrhythmic longitudinal global $Ca^{2+}$ waves in atrial myocytes. In the present study, we further explored underlying cellular mechanism for the shear stress-induced longitudinal global $Ca^{2+}$ wave in isolated rat atrial myocytes. A shear stress of ${\sim}16dyn/cm^2$ was applied onto entire single myocyte using pressurized fluid puffing. Confocal $Ca^{2+}$ imaging was performed to measure local and global $Ca^{2+}$ signals. Shear stress elicited longitudinally propagating global $Ca^{2+}$ wave (${\sim}80μm/s$). The occurrence of shear stress-induced atrial $Ca^{2+}$ wave was eliminated by the inhibition of ryanodine receptors (RyRs) or inositol 1,4,5-trisphosphate receptors ($IP_3Rs$). In addition, pretreatment of phospholipase C (PLC) inhibitor U73122, but not its inactive analogue U73343, abolished the generation of longitudinal $Ca^{2+}$ wave under shear stress. Our data suggest that shear-induced longitudinal $Ca^{2+}$ wave may be induced by $Ca^{2+}$-induced $Ca^{2+}$ release through the RyRs which is triggered by $PLC-IP_3R$ signaling in atrial myocytes.